THE EFFECT OF BUDGET MANAGEMENT AND HUMAN RESOURCE QUALITY ON BUDGET ABSORPTION THROUGH ORGANIZATIONAL COMMITMENT AS A MODERATOR : A CASE STUDY AT THE REGIONAL OFFICE OF THE NATIONAL LAND AGENCY IN EAST NUSA TENGGARA PROVINCE, INDONESIA - Delvia V Naisanu; Petrus Kase; Ajis Salim Adang Djaha (RADJA PUBLIKA, 2026)
This study analyzes the effect of Budget Management and Human Resource Quality on Budget Absorption through Organizational Commitment as a moderating variable in 23 Work Units within the East Nusa Tenggara Provincial Office of the National Land Agency. This study involved 230 respondents who were directly involved in the budget management process. Data analysis was performed using the Partial Least Squares (PLS) based Structural Equation Modeling (SEM) method. The results showed that budget planning, budget implementation, and budget revision had a positive and significant effect on budget absorption, while HR quality had a significant but negative effect on budget absorption. These findings reveal that respondents with higher education levels tend to have greater risk awareness and are therefore more cautious in realizing the budget. In addition, the respondents' competencies, which are not linear with the tasks performed, are considered to hinder the effectiveness of budget absorption. However, the SEM-PLS analysis emphasizes that the magnitude of the influence is determined by the path coefficient value, not by the positive or negative influence. Meanwhile, organizational commitment was not proven to moderate the relationship between budget planning, budget implementation, budget revision, and human resource quality on budget absorption, as evidenced by all insignificant moderation p-values. Overall, the results of the study confirm that budget planning, budget implementation, budget revision, and HR quality play an important role in increasing budget absorption. Therefore, optimization of budget management needs to be accompanied by strengthening HR capacity so that budget absorption performance can be achieved optimally.